Pengaruh Artificial Intelligence dan Pembelajaran Daring terhadap Hasil Belajar Berdasarkan Motivasi dan Minat Mahasiswa - Pipin Yulanda; Etty Indriani (Jurnal Bisnis Manajemen dan Akuntansi (BISMAK), 2025)
The purpose of this study is to explore the influence of Artificial Intelligence and online learning on student learning outcomes at FIKOM UDB Surakarta, taking into account the roles of learning motivation and interest. A quantitative approach was employed, with data collected through questionnaires distributed to 120 students. The findings reveal that Artificial Intelligence significantly affects students’ motivation, interest, and learning outcomes. In contrast, online learning only has a significant impact on motivation and interest, but not directly on learning outcomes. Motivation and Learning Interest play a crucial role as mediators in strengthening the impact of Artificial Intelligence and Online Learning on improving student learning outcomes. Path analysis indicates that the most dominant effect is from Artificial Intelligence on learning outcomes mediated by learning motivation, with a path coefficient of 0.222. The model accounts for 87.3% of the variance in learning outcomes, while the remaining 12.7% is attributed to external factors such as lecturer quality and the learning environment. These results emphasize the critical role of AI technology in enhancing learning effectiveness compared to online learning methods.